2011
DOI: 10.1016/j.scr.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased screening of polymer libraries to define novel substrates for functional hepatocytes with inducible drug metabolism

Abstract: Maintaining stable differentiated somatic cell function in culture is essential to a range of biological endeavors. However, current technologies, employing, for example, primary hepatic cell culture (essential to the development of a bio-artificial liver and improved drug and toxicology testing), are limited by supply, expense, and functional instability even on biological cell culture substrata. As such, novel biologically active substrates manufacturable to GMP standards have the potential to improve cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 25 publications
2
77
0
Order By: Relevance
“…Comparison with adult liver revealed that the hESC-derived cells had levels of the Phase I enzyme genes in the range of 7-27% and of the Phase II gene UGT1A1 at 82% of those found in the adult tissue. Several previous studies have reported the development of hPSC-derived hepatocytes that express some P450 enzyme activity (Duan et al, 2010;Hay et al, 2011;Takayama et al, 2011;Nagamoto et al, 2012;Takayama et al, 2012;Takayama et al, 2013). Duan et al (Duan et al, 2010) were the first to successfully generate cells that had CYP1A2, CYP3A4, CYP2C9 and CYP2D6 enzyme activities comparable with those found in primary hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with adult liver revealed that the hESC-derived cells had levels of the Phase I enzyme genes in the range of 7-27% and of the Phase II gene UGT1A1 at 82% of those found in the adult tissue. Several previous studies have reported the development of hPSC-derived hepatocytes that express some P450 enzyme activity (Duan et al, 2010;Hay et al, 2011;Takayama et al, 2011;Nagamoto et al, 2012;Takayama et al, 2012;Takayama et al, 2013). Duan et al (Duan et al, 2010) were the first to successfully generate cells that had CYP1A2, CYP3A4, CYP2C9 and CYP2D6 enzyme activities comparable with those found in primary hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) are examples of renewable cell populations [9,10]. Both populations have been shown to efficiently differentiate to hepatocytes by either spontaneous or directed differentiation and, therefore, offer significant promise in the quest to deliver a new wave of predictive human models [11][12][13][14][15][16][17][18][19]. In this vein, we have developed highly efficient, scalable, and serum-free differentiation procedures that are compatible with pluripotent stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…This has made them some of the most widely used hESC lines in research, and in particular the most commonly used hESC lines in SCDH research, specifically the H1 and H9 lines [11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. To be useful in preclinical drug metabolism and toxicity screening, SCDHs must demonstrate consistent and reproducible activity of drug metabolism proteins, in particular the oxidative CYP enzymes.…”
Section: Resultsmentioning
confidence: 99%